Understanding the Role of Morningness/Eveningness in Physical Activity Engagement: A Mixed Methods Approach - Nicholson, Lauren Elaine (Curtin University, 2022)
The main objective of this thesis is to explore the psychosocial factors that may prevent or promote individuals to engage in physical activity. In doing so, this thesis will highlight some of the variables that could help individuals increase their engagement in physical activity. These factors can then be incorporated into future interventions, targeted at specific groups. Additionally, the focus of this thesis was to enhance our understanding of the impact that morningness/eveningness may have on individuals’ physical activity routines. These aims were achieved by applying a mixed-methods approach as well as the utilisation of various combined and extended health models. This thesis found that self-efficacy significantly predicted motivation, while perceived behavioural control predicted intention to engage in physical activity. Furthermore, planning, habit, past behaviour and environmental cues were important factors in people being physically active. These findings can help develop behaviour change techniques as well as be used to design interventions that help facilitate an improvement in peoples' physical activity engagement.